2011
DOI: 10.4049/jimmunol.1000148
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Roles of IL-23 and IL-17 in the Development of Psoriasis-Like Lesions in a Mouse Model

Abstract: Psoriasis is an inflammatory disease with dynamic interactions between the immune system and the skin. The IL-23/Th17 axis plays an important role in the pathogenesis of psoriasis, although the exact contributions of IL-23 and IL-17 in vivo remain unclear. K5.Stat3C transgenic mice constitutively express activated Stat3 within keratinocytes, and these animals develop skin lesions with histological and cytokine profiles similar to those of human plaque psoriasis. In this study, we characterized the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
140
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(157 citation statements)
references
References 53 publications
16
140
0
1
Order By: Relevance
“…106 In contrast to targeting IL-23 signaling, the inhibitory effects of targeting IL-17 signaling are less prominent in these animal models, indicating that alternative pathways may also contribute to the development of skin inflammation. 103,104,106 On a cellular level, IL-17 synergizes with other cytokines, such as TNFα, IFNγ or IL-22, to induce the production of proinflammatory cytokines, chemokines and antimicrobial peptides from keratinocytes. [107][108][109] Because the IL-23-Th17-IL-17 axis is critical for the pathogenesis of psoriasis, antibody targeting therapies that target IL-17 signaling (that is, brodalumab, ixekizumab and secukinumab) or IL-23 signaling (that is, ustekinumab, briakinumab, tildrakizumab and guselkumab) are being rapidly developed and have shown prominent outcomes in treating psoriatic diseases in different clinical trials.…”
Section: Il-17dmentioning
confidence: 95%
See 2 more Smart Citations
“…106 In contrast to targeting IL-23 signaling, the inhibitory effects of targeting IL-17 signaling are less prominent in these animal models, indicating that alternative pathways may also contribute to the development of skin inflammation. 103,104,106 On a cellular level, IL-17 synergizes with other cytokines, such as TNFα, IFNγ or IL-22, to induce the production of proinflammatory cytokines, chemokines and antimicrobial peptides from keratinocytes. [107][108][109] Because the IL-23-Th17-IL-17 axis is critical for the pathogenesis of psoriasis, antibody targeting therapies that target IL-17 signaling (that is, brodalumab, ixekizumab and secukinumab) or IL-23 signaling (that is, ustekinumab, briakinumab, tildrakizumab and guselkumab) are being rapidly developed and have shown prominent outcomes in treating psoriatic diseases in different clinical trials.…”
Section: Il-17dmentioning
confidence: 95%
“…[103][104][105] K5.Stat3C transgenic mice in which Stat3 is constitutively activated in keratinocytes develop skin lesions similar to those of human psoriasis. 106 Either neutralization of IL-17 or deletion of the Il17a gene ameliorates 12-O-tetradecanoylphorbol-13-acetate-induced psoriasis in these mice. 106 In contrast to targeting IL-23 signaling, the inhibitory effects of targeting IL-17 signaling are less prominent in these animal models, indicating that alternative pathways may also contribute to the development of skin inflammation.…”
Section: Il-17dmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IL23 has been shown to promote greater keratinocyte proliferation than IL12 [48]. In a phase I study, Nakajima et al showed that treatment of mice with psoriatic plaques with anti-IL23p19 antibodies greatly inhibited epidermal hyperplasia [49]. Based on these results, new humanized IgG monoclonal antibodies (BI655066 [50], guselkumab and tildrakizumab [51] formerly SCH900222 [52]), targeting the p19 subunit of IL23, were developed by several different companies and are currently in phase II clinical studies ( Table 2).…”
Section: P19 Component: a New Target For Blockade Of Il23mentioning
confidence: 99%
“…Interestingly, loss of IL-17 has also been associated with disease susceptibility in part because it has been suggested that the absence of IL-17 results in enhanced production of other proinflammatory cytokines. 1 However, more recent studies have challenged the traditional pathogenic role of IL-17 as a purely proinflammatory cytokine. For instance, increased levels of IL-17 were shown to protect against autoimmune mediated type 1 diabetes in non-obese diabetic mice.…”
mentioning
confidence: 99%